An investigation on the relationship between the occurrence of CMV DNAemia and the development of invasive aspergillosis in the allogeneic stem cell transplantation setting. Issue 4 (13th September 2013) - Giménez, Estela; Solano, Carlos; Nieto, José; Remigia, María José; Clari, María Ángeles; Costa, Elisa; Muñoz‐Cobo, Beatriz; Amat, Paula; Bravo, Dayana; Benet, Isabel; Navarro, David
ABSTRACT Cytomegalovirus (CMV) infection might increase the risk of fungal superinfection in allogeneic stem cell transplant patients. The potential association between the occurrence of CMV DNAemia and the development of invasive aspergillosis in this clinical setting was investigated. The current retrospective observational study included 167 patients undergoing T cell‐replete allogeneic stem cell transplantation. Virological monitoring of active CMV infection was performed by the pp65 antigenemia assay and/or by a plasma real‐time PCR assay. A total of 109 out of 167 patients developed CMV DNAemia. Twenty‐three patients had proven (n = 4) or probable (n = 19) invasive aspergillosis. The occurrence of CMV DNAemia was not significantly associated with the subsequent development of invasive aspergillosis (P = 0.38). Overall, the duration of the episodes of active CMV infection and the peak level of CMV DNAemia within the episodes were comparable, irrespective of whether invasive aspergillosis developed subsequently or not (P = 0.99; P = 0.70, respectively). Peak CMV DNA load in patients with proven or probable invasive aspergillosis who died was higher (median, 5, 461 copies/ml) than that in those who survived (median 1, 179 copies/ml) (P = 0.41). The data argue against the existence of an association between the occurrence of CMV DNAemia and the development of invasive aspergillosis, however, CMV replication, particularly at high levels, might aggravate the prognosis of this disease. J. Med. Virol. 86:568–575, 2014. © 2013 Wiley Periodicals, Inc.